Development and Characterisation of Yoghurt incorporated with Dates (Phoenix Dactylifera Linn) Extract - S, Archana; K B, Divya; SN, Rajakumar; P, Sudheerbabu (Indian Journal of Dairy Science, 2023)
Nowadays, functional dairy products gain more acceptance in the market because of the additional health and nutritional benefits they provide to the consumer. Value addition of dairy products like yoghurt often augments the market value as well as functionality of the product. Dates (Phoenix dactylifera Linn) are natural source of phytochemicals like phenolic acids and flavonoids which are proved to have strong anti-oxidant activity. In this study, the effect of addition of dates extract into yoghurt milk was studied. Hot water extract of dates fruit was added to the yoghurt at different levels (30%, 32%, 34%, and 36%) and the optimum level of addition was selected on the basis of sensory scores obtained from 5 semi trained judges. Significant differences (p